The role of SLC26A4 in bony labyrinth development and otoconial mineralization in mouse models - Ito, Taku; Watanabe, Hiroki; Honda, Keiji; Fujikawa, Taro; Kitamura, Ken; Tsutsumi, Takeshi (Frontiers in Molecular Neuroscience, 2024)
Inner ear malformations are predominantly attributed to developmental arrest during the embryonic stage of membranous labyrinth development. Due to the inherent difficulty in clinically assessing the status of the membranous labyrinth, these malformations are diagnosed with radiographic imaging, based on the morphological characteristics of the bony labyrinth. While extensive research has elucidated the intricacies of membranous labyrinth development in mouse models, comprehensive investigations into the developmental trajectory of the bony labyrinth, especially about its calcification process, have been notably lacking. One of the most prominent types of inner ear malformations is known as incomplete partition (IP), characterized by nearly normal external cochlear appearance but pronounced irregularities in the morphology of the modiolus and inter-scalar septa. IP type II (IP-II), also known as Mondini dysplasia, is generally accompanied by an enlargement of the vestibular aqueduct and is primarily attributed to mutations in the SLC26A4 gene. In the case of IP-II, the modiolus and inter-scalar septa of the cochlear apex are underdeveloped or missing, resulting in the manifestation of a cystic structure on radiographic imaging. In this overview, we not only explore the normal development of the bony labyrinth in mice but also present our observations on otolith mineralization. Furthermore, we investigated the specifics of bony labyrinth and otolith mineralization in Slc26a4-deficient mice, which served as an animal model for IP-II. We ensured that these findings promise to provide valuable insights for the establishment of therapeutic interventions, optimal timing, targeted sites, and preventive measures when considering the management of this condition.